ANALYSIS OF THE USE OF MENDELEY USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH: STUDY IN STUDENTS OF OFFICE ADMINISTRATION EDUCATION IN SURABAYA STATE UNIVERSITY - Dewi Arrohmatuz Zahro; Jaka Nugraha (LPPM STMIK Pringsewu, 2021)
The development of information technology makes it easier for humans to complete work. Work that previously required a lot of manpower to complete can now be completed with the help of technology. As in writing citations, it can be done automatically with the help of the Mendeley Reference Management Software. The purpose of this study is to determine the use of Mendeley in students of the Surabaya State University, Office Administration study program using the Technology Acceptance Model (TAM) approach. The research carried out is quantitative research. The study population is 62 students of the Office Administration Education study program, Surabaya State University. The data analysis tool used is Partial Least Square (PLS). The results of this study are: (1) Attitude towards using has a positive effect and significant on behavioral intention of use, (2) Perceived ease of use has no positive effect and significant on behavioral intention of use, (3) Perceived usefulness has a positive effect and significant on behavioral intention of use, (4) Perceived ease of use has a positive effect and significant on perceived usefulness, (5) Indirectly, Perceived ease of use has a positive and significant effect on behavioral intention of use through perceived usefulness